Strategi Perencanaan Upacara Hari Pendidikan Nasional dalam Mendukung Tata Kelola Pendidikan di Dinas Pendidikan Kota Batu - Aninda Tri Safinatun Najah (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2026)
This study aims to analyze the planning strategy of the National Education Day flag ceremony in supporting educational governance at the Department of Education of Batu City. The background of this study is based on the importance of systematic planning in ensuring the effectiveness of ceremonial educational activities that carry strategic values in strengthening nationalism and educational awareness. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results show that the planning strategy has been implemented systematically, starting from needs analysis, evaluation of previous activities, goal setting, stakeholder involvement, committee formation, to the development of thematic and technical concepts. The implementation of the plan is reflected in the structured execution of the ceremony, which runs orderly and in accordance with established procedures. In terms of service quality, the activity demonstrates a high level of success (approximately 85–90%), particularly in reliability, assurance, and tangible aspects. In conclusion, the planning strategy contributes positively to strengthening educational governance through improved coordination, participation, and management effectiveness.